Macrorchis Rondani 1877 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Macrorchis Rondani, 1877 Macrorchis Rondani, 1877: 17 and 280. Type-species: Musca meditata Fallén, 1825, by original designation. Macrorchis meditata (Fallén, 1825) Musca meditata Fallén, 1825b: 87. Type-locality: no locality given (probably Sweden, Skåne province). Lectotype ♂, NHRS (designated by Pont, 1984b: 289). Siberian records: South Urals (Hennig, 1961a: 510); Urals and West Siberia (Zimin & El’berg, 1970: 560); south part of Tyumenskaya Oblast’, near Onokhino, subtaiga (Veselkin, 1966: 784, 788); Khanty-Mansiyskiy AO, Kondinskoye [as “Tyumenskaya Oblast’, Kondinskoye, 911 km from Tobolsk” in the original] (Lavčiev, 1971: 219); Respublika Sakha: Yakutsk, near mouth of River Aldan (Hennig, 1961a: 510); South Urals, West and East Siberia (Pont, 1986a: 198). General distribution: Palaearctic Region, from Europe east to China and Russia (East Siberia). Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on page 71, DOI:10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926